The Dactylis glomerata (Grass Pollen) Allergen Repertoire for Dogs - Martins, Luís; Marques, Andreia; Martins, Ana; Bento, Ofélia (II International Congress of the Southern European Allergy Societies – Lisbon, 31st March to 2nd April. Proceedings em formato digital. pp 9. (www.seas2011.com), 2011)
Companion animals’ consultation because of allergic diseases is increasing much beyond the common flea bite allergic dermatitis. Several sources of aeroallergens, as well as many food allergens are also frequent causes of allergic reactions, showing different target organs from skin to eye conjunctiva, respiratory or digestive systems. Hypersensitivity reactions studies, mainly from type I, but also from type IV are presenting a grown-up relevance also in veterinary medicine, as shown by the increase of scientific communications in the field. In Pursuit of improved diagnostic guidelines for veterinary allergy diagnosis, the identification of allergens for animals from among allergen sources allergoms, appears as an essential way towards more successful therapeutic measures founded on deeper etiopathological knowledge. Because of the genetic pattern associated to a given population, conditioning individual predisposition, it is also important to know the allergic recognition profile of regional populations for several of the most relevant allergen sources which are, as for humans, mites and grass-pollens. In our study, a group of 13 non subjected to specific immunotherapy atopic dogs from southern Portugal outpatient dermatology and allergy consultation was selected by means of clinical, intradermic tests and specific IgE determination. Dactylis glomerata proteome was separated by isoelectric focusing and allergens for dog were identified by patient serum IgE in Western Blotting. Twenty nine allergens were identified within a pH range from 4 to 9,85, five of them showing in this preliminary study a major recognition in our atopic dog population: pI 5,9; 6,1; 8,15; 8,25 and 9,85. Great heterogeneity was observed between individual patient allergen recognition, with the majority of patients (11 out of 13) showing sensitization to other grass pollen species. Clinical manifestations were mainly dermatological with worsening in Spring and no relation with any specific spectrotype pattern was observed, like what happens in humans. Each patient spectrotype could be associated with an individual pattern of sensitization under genetic modulation or with the frequency and amount of exposure to grass pollen. More patients are being selected for inclusion and further electrophoretic techniques, especially two-dimensional SDS PAGE are being performed to obtain further data.
Keywords: Dactylis glomerata; Grass pollen; Allergy; Allergens; Atopy